2013
DOI: 10.1371/journal.ppat.1003425
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Antimicrobial Peptide from Human Hepatitis B Virus Core Protein Arginine-Rich Domain (ARD)

Abstract: The rise of multidrug-resistant (MDR) pathogens causes an increasing challenge to public health. Antimicrobial peptides are considered a possible solution to this problem. HBV core protein (HBc) contains an arginine-rich domain (ARD) at its C-terminus, which consists of 16 arginine residues separated into four clusters (ARD I to IV). In this study, we demonstrated that the peptide containing the full-length ARD I–IV (HBc147-183) has a broad-spectrum antimicrobial activity at micro-molar concentrations, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 66 publications
3
41
0
Order By: Relevance
“…In addition, we fused eight amino acids (SQSRESQC) to the C terminus of P307 and yielded P307 SQ-8C (Table 1). This modification was based on the observation of an earlier study showing that the lack of these eight amino acids reduces the activity spectrum of the antimicrobial peptide from hepatitis B virus core protein (28). We also generated two additional modifications of P307 SQ-8C : scrambling the sequence of the last eight amino acids to CSQRQSES (P307 CS-8 ); and changing the last amino acid from C to A (P307 SQ-8A ) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we fused eight amino acids (SQSRESQC) to the C terminus of P307 and yielded P307 SQ-8C (Table 1). This modification was based on the observation of an earlier study showing that the lack of these eight amino acids reduces the activity spectrum of the antimicrobial peptide from hepatitis B virus core protein (28). We also generated two additional modifications of P307 SQ-8C : scrambling the sequence of the last eight amino acids to CSQRQSES (P307 CS-8 ); and changing the last amino acid from C to A (P307 SQ-8A ) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The permeability of bacterial membrane upon peptide treatment was measured by SYTOX green uptake (28). Briefly, overnight cultures of bacteria were washed and resuspended to ϳ10 7 CFU/ml in 50 mM Tris-HCl (pH 7.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with our previous studies of R-to-K substitutions in HBc ARD (32). difficulty in testing this hypothesis in HBV by in vivo experiments is related to the multiple overlapping functions of the ARD domain in the life cycle of HBV, including capsid assembly/disassembly (29,62), RNA encapsidation (10,11,30,32), core protein trafficking (57,58,(64)(65)(66), DNA synthesis (9-13, 32, 62, 63, 67), and antimicrobial activity (68). Given such an extreme degree of functional complexity associated with a very short HBc ARD domain (HBc 147-183), it is conceivable that attempts to dissociate nucleic acid chaperone activity of HBc ARD from its many other reported functions in vivo will be very challenging in the future.…”
Section: Figmentioning
confidence: 99%
“…They showed that a peptide containing the complete ARD I-IV (HBc 147-183) acts antimicrobially at micromolar concentrations against some multidrugresistant pathogens, including colistin-polymyxin E-resistant Acinetobacter baumannii [43]. It was also determined that the peptides ARD II-IV (HBc 153-176) and ARD I-III (HBc 147-167) showed activity against P. aeruginosa and K. pneumoniae.…”
Section: The Application Of Peptides In Ophthalmologymentioning
confidence: 99%